Strategic Engagement and Legal Pluralism: Navigating Knowledge and Expertise in Mining Disputes - Phillips, Sara K. (วารสารสังคมศาสตร์ จุฬาลงกรณ์มหาวิทยาลัย, 2026)
This article explores how community and civil society actors in mining conflicts strategically engage with legal and technical vocabularies to assert legitimacy, contest exclusion, and influence mining governance. Drawing on an empirical case study of Thailand’s Chatree gold mine, the article analyzes how affected groups navigate overlapping normative systems, such as state law, transnational norms, and technocratic discourses, through informal learning and strategic appropriation of expert language. Framed through the conceptual lens of legal pluralism, the study highlights how actors interpret and mobilize diverse normative orders to articulate grievances, shape narratives, and attempt to gain access to decision-making spaces. These engagements unfold across scalar dimensions, from local to international levels, reflecting both selective alignment with, and resistance to, dominant legal and institutional frameworks. By foregrounding norm contestation and plural authority, the article contributes to socio-legal scholarship on resource conflict, illustrating how actors operate in contexts of institutional distrust to advance alternative visions of justice, development, and legitimacy in sites of mineral resource development.